Supramolecular Organocatalysis in Water Mediated by Macrocyclic Compounds - De Rosa, Margherita; La Manna, Pellegrino; Talotta, Carmen; Soriente, Annunziata; Gaeta, Carmine; Neri, Placido (Frontiers in Chemistry, 2018)
In the last decades many efforts have been devoted to design supramolecular organocatalysts able to work in water as the reaction medium. The use of water as solvent provides promising benefits with respect to environmental impact. In this context, macrocyclic compounds played a role of primary importance thanks to their ease of synthesis and their molecular recognition abilities toward the reactants. The aim of this review is to give an overview of the recent advances in the field of supramolecular organocatalysis in water, focusing the attention on calixarene and cyclodextrins derivatives. Calixarenes and cyclodextrins, thanks to their hydrophobic cavities, are able to host selectively the substrates isolating they from the reaction environment. In addition, the synthetic versatilities of these macrocycles permits to introduce useful functional groups in close proximity of the hydrophobic binding sites. Regarding the cyclodextrins (CDs), we have here reviewed the their most recent uses as organocatalysts for the synthesis of heterocyclic compounds, in multi-component reactions and in carbon-carbon bond forming reactions. Examples have been reported in which CD catalysts are able to drive the regiochemistry of common organic reactions. In addition, cyclodextrins bearing catalytically active chiral groups, have shown excellent enantioselectivity in the catalysis of organic reactions. Recently reported results have shown that calixarene derivatives are able to accelerate organic reaction under "on-water" conditions with a significant selectivity toward the reactants. Under "on-water conditions" the hydrophobic effect, induced by insoluble calixarene derivatives, forces the reactants and the catalyst to aggregate and thus accelerating the reaction between them thanks to an amplification of weak secondary interactions. Regarding the use of water-soluble calixarene organocatalysts, we have here reviewed their role in the acceleration of common organic reactions.